2010
DOI: 10.4271/2010-01-1213
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics and Effects of Lubricant Additive Chemistry on Ash Properties Impacting Diesel Particulate Filter Service Life

Abstract: Ash accumulation in diesel particulate filters, mostly from essential lubricant additives, decreases the filter's soot storage capacity, adversely affects fuel economy, and negatively impacts the filter's service life. While the adverse effects of ash accumulation on DPF performance are well known, the underlying mechanisms controlling these effects are not. To address these issues, results of detailed measurements with specially formulated lubricants, correlating ash properties to individual lubricant additiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(30 citation statements)
references
References 17 publications
1
29
0
Order By: Relevance
“…In Malaysia, the natural sources of silicate and non-silicate minerals in soil are Al and Fe, which are derived from kaolinite, gibbsite, goethite, and hematite (Tessens and Shamshuddin 1983). Zn is added as an additive in lubricants, and it reduces tire wear and corrosion in automotive exhaust systems (Sappok et al 2010). Pb, which mostly involves aerosol combustion products in vehicle releases close to roadways, is initially deposited within about 50 m of a roadway if no obstructions are present.…”
Section: Methodsmentioning
confidence: 99%
“…In Malaysia, the natural sources of silicate and non-silicate minerals in soil are Al and Fe, which are derived from kaolinite, gibbsite, goethite, and hematite (Tessens and Shamshuddin 1983). Zn is added as an additive in lubricants, and it reduces tire wear and corrosion in automotive exhaust systems (Sappok et al 2010). Pb, which mostly involves aerosol combustion products in vehicle releases close to roadways, is initially deposited within about 50 m of a roadway if no obstructions are present.…”
Section: Methodsmentioning
confidence: 99%
“…Also a 2008 study by Sappok gives a novel accelerated aging system to study lubricant additive effects on diesel aftertreatment system degradation [31]. Sappok used this system to study the effects of lubricant additive chemistry on ash properties impacting diesel particulate filter service life in 2010, and concluded that additives like ZDDP, Ca affecting the filter performance in different manners [32]. The objective of this study is to determine the influence of an anti-wear oil additive on diesel engine particle emissions, focus on the changes in physical characters like morphology, size distribution.…”
Section: Introductionmentioning
confidence: 98%
“…Enrichment of heavy metals in the surface soil indicates an association with vehicle traffic and emissions in the surface soil. Zn is added as an lubricant additives to function as corrosion and oxidation inhibitors (Sappok et al 2010). However, according to Najib et al (2012) and Ghazali (2010), there are no soil standards and protocols in Malaysia to evaluate the level of contamination in soil using the bioavailability of heavy metal concentrations.…”
Section: Resultsmentioning
confidence: 99%
“…The total and bioavailability concentration of Zn is the third highest found in the surface soil of the Klang district. Zn is added as an additive in lubricants and for reducing tire wear and corrosion in automotive exhaust systems (Sappok et al 2010). Anor and Ahmad (2010) showed that the Klang area faces high traffic volume, especially during peak hours (weekdays and after office).…”
Section: Multivariate Analysismentioning
confidence: 99%